Conditional expectation operator on the space of measurable sections - Ganiev, Inomjon; Shahidi, Farruh (American Institute of Physics (AIP), 2015)
We prove the existence of conditional expectation operator on the space of measurable sections. We also study the basic properties and prove Jensen’s inequality for conditional expectation operators